Analisis Tingkat Kesehatan Bank KBMI I Sebelum dan Saat Pandemi Covid-19 - Salma Caesaria (2022)
The Covid-19 pandemic has had an impact on all sectors, especially banking. The level of bank soundness is one of the most important factors that must be carried out at every bank. This writing focuses on banks that have a core capital of less than 1 trillion rupiah with the category of Bank KBMI I which is likely to have a higher risk than other bank categories. The purpose of this paper is to be able to see the condition of Bank KBMI I before and during the covid-19 pandemic whether it can be said to be healthy or not by comparison. In assessing the soundness of the bank using a risk-based approach to Risk-Based Bank Rating (RBBR) using the RGEC method which includes 4 components consisting of a Risk Profile consisting of Noan Performing Loan (NPL) and Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Earning which consists of Return On Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM) and Operating Expenses and Operating Income (BOPO) and Capital which is calculated based on the Capital Adequency Ratio (CAR).